ELECTROMYOGRAPHY AND INSTRUMENTATION IN PATIENTS WITH IDIOPATHIC SCOLIOSIS - ANDERSON ALVES DIAS (Coluna/Columna)
ABSTRACT Objective: The objective of this study is to relate the use of intraoperative electromyography with surgical time, proper placement of screws, type of curve and time spent per screw in idiopathic scoliosis correction surgery in a group of surgeons from Belo Horizonte. This study used the database of protocol evaluation of patients operated in the service, and separately analyzed the results of motor and somatosensory potentials. Methods: Retrospective study of 80 patients undergoing surgery for correction of idiopathic scoliosis between December 2008 and January 2015. A single group of Belo Horizonte spine surgeons performed the intraoperative electromyographic (EMG) monitoring. EMG was performed with stimulation of pedicle screws in patients undergoing instrumentation with pedicle screws as fixation elements. Results: The sample consisted of 85% females (mean age 17 years) and 37.5% of cases had classification type 1AN of Lenke. Of the total surgical cases, 60% had EMG changes. Of the total cases analyzed, 66.3% were true positives for the result. Conclusion: Intraoperative monitoring with EMG is a very important tool for the surgical treatment of patients with scoliosis undergoing instrumentation with pedicle screws. It enables to check if the screw is located on the correct path, helping to decrease the error rate and providing corrections to the surgical approach through a change of strategies. Moreover, it contributes to decrease the time to screw positioning and the total surgical time.